2021
DOI: 10.33902/ijods.2021269755
|View full text |Cite
|
Sign up to set email alerts
|

Adversity and emotional quotients of public elementary school heads amidst the COVID-19

Abstract: This study aimed to identify the relationship of adversity quotient and emotional quotient amongst public elementary school heads. The study employed a descriptive-correlation research design with the online survey as primary data collection tool. The respondents came from the 25 elementary schools in a Schools Division Office in Central Luzon. 25 elementary school heads participated in the online survey using universal sampling technique. Adapted questionnaires were used to gather data. For the statistical tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Distance Education may seem very significant nowadays, specifically to those learners who can't go to school for their face-to-face class. Hence, this significant factor has uncertainties as regards to the misuse of the technology, the attitudes of learners, since students tend to procrastinate [4] and bully teachers [5] [6] [7], administrators' behavior and competencies [8] [9] and most of all the quality of instructions [10] [11]. According to another study students perceived distance education as a road to dreams and they thought it provided them to study while working in a job [12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Distance Education may seem very significant nowadays, specifically to those learners who can't go to school for their face-to-face class. Hence, this significant factor has uncertainties as regards to the misuse of the technology, the attitudes of learners, since students tend to procrastinate [4] and bully teachers [5] [6] [7], administrators' behavior and competencies [8] [9] and most of all the quality of instructions [10] [11]. According to another study students perceived distance education as a road to dreams and they thought it provided them to study while working in a job [12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, such professional conduct and attribute by the teachers will evade any forms of inappropriate behavior like bullying from students [10] [11]. It is essential for a leader, especially school heads, to understand and recognize the mentality, stress, emotions, work attitudes, as well as the performance of their teachers [12] [13]. In this manner, a harmonious working environment and climate may ensue [14] and organizational satisfaction [15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, the pandemic cultivated creativity and innovation among teachers so that their learning resources will have an impact on the learners even if there is a pandemic. Teachers' mental health has become an attribute of all school leaders to remain healthy (physically, socially, psychologically, and socially) as a result of the pandemic, and has been proven to have a major influence on teachers' learning resource development (Jimenez, 2021a). To make learning and teaching interesting and engaging, teachers have the option to create and develop extra activities as well as document the outcomes of sessions (McLeod, 2020).…”
Section: "In Our City Schools Division Of Meycauayan We Had Lots Of Learning Resources Aside From Adm From Region Our Hardworking Lr Supementioning
confidence: 99%
“…The presence of learning resources from the CO became the main issue of all teachers and divisions in the Central Luzon Region due to lack of preparation time and the prohibition of physical contact which caused delays and insufficiencies of the ready to print learning resources. This situation tested the adversity capacity of school heads on which a study showed an above average result (Jimenez, 2021a) Considering these constraints, different School Division Offices (SDOs) have taken the initiative to encapsulate the development of locally developed learning resources within their area. As a result of such a daring move, certain contexts of professional skills (Asio & Riego de Dios, 2018; 2019) and work ethics among teachers, as well as supervisory rapport for administrators , were enhanced.…”
Section: Introductionmentioning
confidence: 99%